Frequency of Destructive Hip Disease Post Intra-Articular Cortecosteroid Hip Injection - Abbas Ali, Syed Bakht Sardar, Abedullah Khan, Kamran Saeed, Mushtaque Ahmed Shaikh, Manqoosh Ur Rehman, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study aims to quantify the prevalence of destructive hip disease following intra-articular corticosteroid hip injections. Study design: A retrospective study Place and duration of study: Department of Orthopaedic, Khyber Teaching Hospital Peshawar during the period from January, 2022 to June, 2022. Methods: This study was conducted on two hundred cases of corticosteroid injection treatment. For finding the frequency of destructive hip disease, the radiological imaging was used. Patients were compared with their clinical, paraclinical, and demographic data. Observations of pain, joint mobility, and radiographic evaluation served as the foundation for the recently suggested clinico-radiological diagnostic criteria. The inter- and intraobserver reliability of the radiological grading system was evaluated. For statistical analysis, SPSS-20 was employed.. Results: From the total 200 cases, patients with POH were 80(40%), with RPOH were 20(10%), with femoral head avascular necrosis were 20(10%) and with secondary osteoarthritis of hip were 40(20%), patients went for THA were 90%. There were 30% males and 160% females with mean age of 53.9 ±3.3 and BMI >32. The corticosteroidal injection of 40mg triamcinolone-acetonide with 4 mL 1% lidocaine was placed in 21(77.8%). Conclusion: An elevated chance of quickly degenerative hip disease can result from intra-articular corticosteroid hip injection. Hip injections with intra-articular corticosteroids are probably not as safe as we had believed. Hip injections should only be used when absolutely necessary, and their usage should be reduced. Before administering a large and repeated dose of corticosteroids, the patient should also be warned about the possibility of the condition progressing faster. Keywords: RDHD, intra-articular corticosteroid hip injection, frequency.